2017
DOI: 10.1093/annweh/wxx020
|View full text |Cite
|
Sign up to set email alerts
|

Wood Dust in Joineries and Furniture Manufacturing: An Exposure Determinant and Intervention Study

Abstract: Wood dust exposure is high in joinery workers and (to a lesser extent) furniture makers with frequent use of hand tools and cleaning being key drivers of exposure. Vacuum extraction on hand tools and alternative cleaning methods reduced workplace exposures substantially, but may be insufficient to achieve compliance with current occupational exposure limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In their study, electric belt sander with cotton cloth filter bag was used to sand beech wood and they reported reduction in airborne dust concentrations ranging from 66 to 72%. On the contrary, Douwes et al [6] showed that the use of integral dust extraction unit caused increase of airborne aerosols. However, their laboratory experiment involved sanding medium density fibreboard using the different type of sander with finer grain size of abrasive.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In their study, electric belt sander with cotton cloth filter bag was used to sand beech wood and they reported reduction in airborne dust concentrations ranging from 66 to 72%. On the contrary, Douwes et al [6] showed that the use of integral dust extraction unit caused increase of airborne aerosols. However, their laboratory experiment involved sanding medium density fibreboard using the different type of sander with finer grain size of abrasive.…”
Section: Discussionmentioning
confidence: 98%
“…Results from these studies indicate that personal exposures to dust are substantially lower when on-tool systems for sanding dust collection were used. On the contrary, Douwes et al [6] reported that the application of integral dust extraction unit to orbital sander was useless in decreasing exposure to wood dust. The objective of this pilot study was to assess the performance of commercially available dust collection box at decreasing exposure to wood aerosol during sanding spruce wood with handheld power belt sander.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, as early as 1995, the International Agency for Research on Cancer (IARC) classified WD as “carcinogenic to humans (Group 1)”, considering the increasing risk in subjects exposed to WD in developing cancers of the nasal cavities and paranasal sinuses [ 2 ]. Nevertheless, non-malignant respiratory effects could also occur, including, among the others, upper and lower respiratory tract symptoms and inflammation and occupational asthma [ 5 ]. In vitro exposure to fine particulate matter may lead to the increased production of Radical Oxygen Species (ROS) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…They evaluated national level interventions with inconclusive results. Two intervention studies assessed reduction in dust exposure, but they did not relate exposure to health outcomes ( Lazovich et al , 2002 ; Douwes et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%